The role of the Islamic solidarity sector in achieving sustainable development in the Kingdom's Vision 2030 (International Journal of Financial, Administrative and Economic Sciences, 2025)
The Kingdom's Vision 2030has adopted the use of Islamic principles in its development programs and initiatives. Therefore, it has been keen to involve the solidarity sector in participating in achieving the Sustainable Development Goals. This study aimed to clarify the role of the Islamic solidarity sector in achieving sustainable development in the Kingdom's Vision 2030. The study concluded with some results, the most important of which is that the Vision's programs and initiatives seek to increase the contribution of the Islamic solidarity economy by supporting the growth of the non-profit sector, enabling non-profit organizations to achieve a deeper impact, and encouraging volunteer work. The integration between the solidarity and for-profit sectors has positive effects in terms of increasing economic contribution and social development. Solidarity sector institutions such as endowments, cooperative societies, and social development committees stand out in supporting many programs and initiatives with social and economic impact. Therefore, the Islamic solidarity sector plays an important role in achieving sustainable development in the Kingdom's Vision 2030 through the programs and initiatives it offers through several different entities, such as quality of life programs, economic diversification, and the preservation of natural resources.
Keywords: Islamic Solidarity Economy; Sustainable Development; Kingdom Vision 2030; Non-Profit Sector